(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
The article explains the role of greening of agriculture in terms of rational use and protection of natural resources, as well as improving the quality of natural environment. Agriculture greening is a new stage of culture, which provides a transition from the consumption principle to careful nature use, refusing the extensive use of natural resources.